The Proportion of Radiation Pneumonitis among Lung Cancer Patients in Persahabatan Hospital - Dini Rizkie Wijayanti; Jamal Zaini; Achmad Hudoyo; Aziza Ghanie; Westi ATW (National Cancer Center - Dharmais Cancer Hospital, 2020)
Background : Radiation-induced pulmonary toxicity occurs in patients with lung cancer who received irradiation. The objective of this study was to determine the proportion of radiation pneumonitis among lung cancer patients that were exposed to radiation treatment in Persahabatan Hospital. There is no data about proportion of radiation pneumonitis in Indonesia.Methods: This was a retrospective study conducted in Persahabatan Hospital during June 2013– July 2015 using the medical record of lung-cancer patients who received irradiation.Results: 33 lung-cancer patients fulfilled the inclusion criteria. Most of them were male (66.7%), in age ≥ 51 years (63.6%), had a smoking history (75.8%) with moderate Brinkman Index (60%), were given irradiation doses of 3,000–4,000 (60.6%) with irradiation fractions of 10–19 (60.6%), had no history of chemotherapy (54.5%), and were diagnosed with adenocarcinoma (66.7%) and stage-IV cancer (84.84%). The proportion of radiation pneumonitis based on chest X-ray (CXR) was 39.4%; which consisted of hazy ground-glass opacities, hazy ground-glass opacities, and fibrosis, and only fibrosis. There were significant differences in age, radiation doses, and history of chemotherapy with the proportion of radiation pneumonitis (p < .05).Conclusion: The proportion of radiation pneumonitis based on CXR was 39.4%. There were significant differences in age, radiation doses, and history of chemotherapy with the proportion of radiation pneumonitis.